Analyzing the Right to Health and Education and Health for People With Disability - Christine Milly Achii (Uganda Christian University, 2024)
Article 24 and 251 provide for the right to education and health of persons with disability respectively. States are mandated to while fulfilling their obligation towards rights of person with disability to do so by equalization of opportunities means ensuring that the various systems of society and the environment, such as services, activities, information and documentation, are made available to all, particularly to persons with disabilities. Aside from the Convention of rights of persons with disabilities, there are other regional laws that provide for the right to education and health of persons with disability. The Protocol to the African Charter on Human and People’s Rights of Persons with Disabilities in Africa under Article 16 and 17 provides for the right to education and health of persons with disability respectively. The right to health and education of persons with disabilities is adopted into Uganda’s legislation under section 6 and 7 prohibiting any form of discrimination on the basis of disability. However there is still limited access to health and education by persons with disabilities; this is mainly as a result of poor education and health structure. Lack of trained personnel in giving assistance to persons with disabilities and stigmatization by society. Government should create awareness to members of societies and above all infuse training of medical and educational professionals on how to treat and educate members with disability in the very fabric of the journey and education of becoming teachers and medical personnel as a course of its own.